Biomarkers in the diagnostic algorithm of myalgic encephalomyelitis/chronic fatigue syndrome - Gravelsina, Sabine; Vilmane, Anda; Svirskis, Simons; Rasa-Dzelzkaleja, Santa; Nora-Krukle, Zaiga; Vecvagare, Katrine; Krumina, Angelika; Leineman, Iana; Shoenfeld, Yehuda; Murovska, Modra (Frontiers in Immunology, 2022)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex disease that is mainly diagnosed based on its clinical symptoms. Biomarkers that could facilitate the diagnosis of ME/CFS are not yet available; therefore, reliable and clinically useful disease indicators are of high importance. The aim of this work was to analyze the association between ME/CFS clinical course severity, presence of HHV-6A/B infection markers, and plasma levels of autoantibodies against adrenergic and muscarinic acetylcholine receptors. A total of 134 patients with ME/CFS and 33 healthy controls were analyzed for the presence of HHV-6A/B using PCRs, and antibodies against beta2-adrenergic receptors (β2AdR) and muscarinic acetylcholine receptors (M3 AChR and M4 AChR) using ELISAs. HHV-6A/B U3 genomic sequence in whole-blood DNA was detected in 19/31 patients with severe ME/CFS, in 18/73 moderate ME/CFS cases, and in 7/30 mild ME/CFS cases. Severity-related differences were found among those with a virus load of more than 1,000 copies/106 PBMCs. Although no disease severity-related differences in anti-β2AdR levels were observed in ME/CFS patients, the median concentration of these antibodies in plasma samples of ME/CFS patients was 1.4 ng/ml, while in healthy controls, it was 0.81 ng/ml, with a statistically significant increased level in those with ME/CFS (p = 0.0103). A significant difference of antibodies against M4 AChR median concentration was found between ME/CFS patients (8.15 ng/ml) and healthy controls (6.45 ng/ml) (p = 0.0250). The levels of anti-M4 plotted against disease severity did not show any difference; however, increased viral load correlates with the increase in anti-M4 level. ME/CFS patients with high HHV-6 load have a more severe course of the disease, thus confirming that the severity of the disease depends on the viral load—the course of the disease is more severe with a higher viral load. An increase in anti-M4 AchR and anti-β2AdR levels is detected in all ME/CFS patient groups in comparison to the control group not depending on ME/CFS clinical course severity. However, the increase in HHV-6 load correlates with the increase in anti-M4 level, and the increase in anti-M4 level, in turn, is associated with the increase in anti-β2AdR level. Elevated levels of antibodies against β2AdR and M4 receptors in ME/CFS patients support their usage as clinical biomarkers in the diagnostic algorithm of ME/CFS.